Case report: Changes in serum bevacizumab concentration in a hemodialysis patient with unresectable colorectal cancer treated with FOLFIRI plus bevacizumab - Tanaka, Toshimitsu; Suzuki, Hiroyuki; Ushijima, Tomoyuki; Nagasu, Sachiko; Akagi, Yoshito; Kawaguchi, Takumi; Miwa, Keisuke (Frontiers in Oncology, 2022)
The global incidence of colorectal cancer (CRC) in patients receiving hemodialysis is steadily rising. However, current information on the clinical use of chemotherapy for hemodialysis patients with CRC is limited. Herein, we describe a clinical course of a 74-year-old hemodialysis patient with unresectable CRC treated with folinic acid, 5-fluorouracil (5FU), and irinotecan (FOLFIRI) plus bevacizumab. whose transiation of serum bevacizumab concentrations were analyzed. Treatment was initiated with a standard dosage of 5-FU and 80% of the standard dose of irinotecan to avoid any adverse events. However, neutropenia (grade 4) was observed after five treatment cycles, which prompted a dose reduction of 5-FU and irinotecan, after which the treatment was safely completed. Moreover, progression-free survival of the patient was 7.5 months. Changes in serum bevacizumab concentrations were similar to those documented in patients with normal renal function. In addition, no bevacizumab-related adverse events occurred in the current report. It was inferred that FOLFIRI plus bevacizumab therapy can be implemented as a safe and efficient treatment for hemodialysis patients with unresectable CRC. To the best of our knowledge, this is the first report to analyze serum bevacizumab concentrations in hemodialysis patient with unresectable CRC.